O valor da raiva: as funções ético-normativas e políticas da emoção em contextos de injustiças sociais - Bello, Letícia da Silva (2022)
The present dissertation aims to investigate the ethical and political role of anger in scenarios of social injustices, by systematizing the contemporary philosophical debate about the emotion. This debate comprehends a myriad of arguments that can be divided in two groups: those that write a critique of anger from the moral and political perspective, and those that defend the presentation of anger on both spheres. In the first group there is Martha Nussbaum’s thesis (2016), which sustains that anger is essentially a retributive emotion and, therefore, it is normatively problematic and politically counterproductive. On the other hand, the arguments in favor of anger come from traditions of feminist and anti-racist authors that consider the individuals that are part of socially oppressed groups. In these traditions, anger plays a central role as a claim for recognition of injustices, and has an important role as a detector of social injustices, as well as a motivator of social action. Those opposite perspectives have been generating great and continuous productions in contemporary moral, political and social philosophy, and the present work systematizes this debate in order to characterize its ramifications and to develop a limited defense of one of the positions present in the literature. Therefore, this work presents a general guide about what constitutes anger, by beginning with an analysis of its cognitive, phenological, expressive and comportamental components, examining their implications on the ethical and political debate about the emotion. The pluralistic perspective of anger is analyzed, as opposed to the retributive perspective. Then, the moral debate of anger is systematized and analyzed, starting with the normative critique of the emotion, developed by Martha Nussbaum (2016), and then the defenses of anger that sustains its validity by considering moral agents that are socially oppressed. Finally, anger is analyzed as a productive emotion for the search of social justice, emphasizing an opposition with the criticism of the ineffectiveness of anger developed by Nussbaum (2016), and therefore defending the epistemic and motivational role of emotion.